Estresse parental em mães de bebês, crianças e adolescentes com paralisia cerebral - Ribeiro, Maysa Ferreira Martins (2013)
This thesis follows the scientific article model. The first article, “Parental stress in families of children with cerebral palsy: an integrative review”, was submitted and accepted for publication in the journal Ciência & Saúde Coletiva. Objectives: to select, evaluate and interpret critically the bibliographic production focused on the stress experienced by parents/caregivers of children with cerebral palsy. Methods: an integrative literature review. Sources for this search were the Virtual Health Library (VHL), the United States National Library of Medicine (PubMed) and manual search of references from the selected studies. We opted to select studies published between 1998 and 2011. Results: the sample included 13 articles. Parents of children with cerebral palsy have higher stress levels than parents of children without disabilities. Behavioral problems, psychological disorders and emotional needs of children were factors commonly associated with high levels of stress. Satisfaction with social support, self-satisfaction with the parental role, a good family functioning, an emotional bond between father/mother and child, the spousal support and the sense of being an active participation in social life help reduce stress levels. The second article, “Parental stress in mothers of babies, children and adolescents with cerebral palsy”, will be submitted to Revista Latino-Americana de Enfermagem. Objectives: a) evaluate the parental stress in mothers with cerebral palsy; b) to verify variations in parental stress among mothers of children with mild motor impairment (levels I/II on the Gross Motor Function Classification System - GMFCS) and severe motor impairment (GMFCS levels IV/V); c) to evaluate the parental stress level in mothers whose children are classified at levels I, II, IV and V on the GMFCS and check the influence of motor impairment on the maternal stress; d) assess variations in parental stress among mothers of adolescents with cerebral palsy classified at levels I / II and IV / V of the GMFCS; e) to check if the parenting stress varies according each stage of child’s: infancy, childhood and adolescence; f) to relate the parental stress with socio-demographic variables: mother age, education, family income, profession/job, marital status, number of children, kind of transportation, participation in leisure activities and psychological support. Methods: analytical cross-sectional study with 223 mothers of babies, children and adolescents with cerebral palsy. The parenting stress was measured by the Parenting Stress Index Short Form (PSI / SF), that consists of 36 items which comprise three subscales. Método: Cross-sectional, descriptive study with 223 mothers of babies, children and adolescents with cerebral palsy. The parenting stress was measured by the Parenting Stress Index Short Form (PSI/SF), that consists of 36 items which comprise three subscales. Results: a) 45.3% of the mothers had high level of parental stress; b) mothers of children at GMFCS Levels I/II had higher stress level on the subscale "difficult child" whose issues are related to children’s behavior; c) among mothers of children at GMFCS Level V the stress was high for all the questionnaire, revealing that it comes from a broad context that includes mothers’ and children’s characteristics and how they cope with the demands; d) mothers of adolescents in levels I / II were more stressed than mothers of adolescents in levels IV / V; e) levels of parental stress vary according to children development stage; mothers of children were more stressed than mothers of babies and adolescents; f) paid work and leisure contribute to stress reduction. Conclusion: mothers of infants, children and adolescents with cerebral palsy, whose sons have motor impairment, from mild to severe, are vulnerable to parental stress. Paid work and leisure activities were the factors that contributed most to reduce stress.